482 New Zealand Rural Hospital Junior Doctor General Surgery Guidelines for Emergency Department (ED): every little helps. (4th May 2021) - Keren, B; Voll, J; Herewini, A; Paranawidana, R; Prasad, J; Collins, D
Abstract: Introduction: Clinical guidelines are associated with improved patient outcomes. This is especially true for junior staff members with little clinical experience. We created Pocket Guidelines for the management of surgical patients in ED, aimed at house officers. Method: Seventeen common surgical conditions were selected for guidelines. Information was collated on presentation, exam findings, differential diagnosis, laboratory tests, imaging, indications for referral, and timing. Evidence based guidelines were approved by General Surgical consultants in the department. The utility of our guidelines was assessed by surveying 20 junior doctors. Results: 16 out of 20 house officers responded to the survey, ranging from post graduate year (PGY) 1 to 4, majority of them (37.5%) being PGY1. 69% were female and 31% were male. A 5- point Likert scale was utilised for answers. No house officers 'strongly agreed' with being confident in managing surgical conditions in ED. Over 80% strongly agreed with the need to have ED clinical guidelines for surgical patients. Over 90% of house officers, having studied the pocket guidelines, found these useful. Conclusions: We implemented pocket guidelines for general surgery in a rural hospital ED to streamline surgical admissions. Guidelines were found to be beneficial by the majority of junior doctors.